Determinantes da entrada das mulheres no tráfico de drogas: um estudo para o Acre (Brasil) - Amaral, Josineide Aquino da Silva (2019)
The general objective of this work was to identify and analyze the determinants of women's entry into the drug trafficking crime that are serving a sentence or awaiting trial at the Rio Branco Women's Prison, Acre. To achieve this goal, 146 questionnaires/interviews were conducted with prison inmates. Data were qualitatively analyzed using descriptive and focal group statistics and quantitatively using econometric analysis. The main characteristics of the woman who committed the crime of drug trafficking were: brown, aged between 18 and 28 years old, believes in God, used alcohol, used drugs and smoked at the time of the crime, has high school complete. The mother had only the elementary school and the father was illiterate, the parents were separated, was cohabiting, lived with husband and/or children, lived in non-violent neighborhood, is a repeat offender and has family members with criminal record, especially siblings. As for the modus operandi, she had no weapon in criminal action and had no partners to commit the crime. The idea of easy gain was the main motivation for entering the crime and denunciation (stoolie) was the most cited reason for the failure of illicit activity. The cost-benefit ratio of crime has shown that women make a rational choice between licit and illicit work, because for them the benefits outweigh the costs and they have a perceived profit from it. It should had be noted that these women's social relationships also influenced their entry into trafficking. Logistic regression evidenced five variables that positively or negatively influence women's entry into trafficking: income negatively influences women's entry into this activity, the higher the income, the lower the likelihood of trafficking. Another variable that decreases the probability of trafficking for these women was family violence. The variables love involvement with traffickers, profit from crime and adolescent crime increase the likelihood of entering drug trafficking. A woman who has love involvement with drug traffickers, has a perception of profit from trafficking, committed adolescent crimes and suffered no family violence is 80.3% probability to commit the crime of drug trafficking.